2019
DOI: 10.13189/ujer.2019.070216
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of English Teachers in Turkey and Germany

Abstract: We can assert that teachers have a key role for the success of program implementations. Also, the compatibility of beliefs and pedagogical practices of the teachers is significant. Analyzing the perceptions of teachers on programs in different countries may provide us with comparative lenses to comprehend how primary English programs are applied in each country and teachers' beliefs about English teaching. Therefore, the aim of this study is to compare the perceptions of English teachers on primary school Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Training effective teachers has also been identified as a major obstacle to effective FL education in Turkey. Although FL teachers as the only source of exposure to English are critical agents modeling their students effective FL use (Çelik, Arıkan, & Caner, 2013), dramatic discrepancies are still common phenomena between the methodological approaches prescribed in teacher education programs and teacher practices in FL classrooms (Gedikoğlu, 2005;İnci & Yıldız, 2019;Karcı & Akar-Vural, 2011). A closer investigation into the problem of FL teachers and their training revealed that such discrepancies were only tip of the iceberg as the roots of the problem seemed to be entrenched deeply in more macro level elements like a predominantly theory-oriented teacher training, lack of a consistent continued professional development policy, teacher employment and induction procedures, and an unsystematic mentoring system.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Training effective teachers has also been identified as a major obstacle to effective FL education in Turkey. Although FL teachers as the only source of exposure to English are critical agents modeling their students effective FL use (Çelik, Arıkan, & Caner, 2013), dramatic discrepancies are still common phenomena between the methodological approaches prescribed in teacher education programs and teacher practices in FL classrooms (Gedikoğlu, 2005;İnci & Yıldız, 2019;Karcı & Akar-Vural, 2011). A closer investigation into the problem of FL teachers and their training revealed that such discrepancies were only tip of the iceberg as the roots of the problem seemed to be entrenched deeply in more macro level elements like a predominantly theory-oriented teacher training, lack of a consistent continued professional development policy, teacher employment and induction procedures, and an unsystematic mentoring system.…”
Section: Review Of Literaturementioning
confidence: 99%